2007
DOI: 10.1097/ijg.0b013e31802dfc35
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cataract Extraction on SITA Perimetry in Patients With Glaucoma

Abstract: In glaucoma patients examined with SITA-standard, MD improved but PSD change was statistically nonsignificant, after the cataract surgery. SITA-standard PSD can be used to monitor glaucoma progression in patients with coexisting glaucoma and cataract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The authors of GPA have attributed this same fact21 to the greater sensitivity of the Progressor program with respect to the GCP software 22. However, recent studies have observed that the change in MD after cataract operation is small,23 In patients with glaucoma, using the SITA-standard strategy we have observed that cataract removal improves MD by about 1.2 dB on average 24. A similar result was reported after cataract surgery in the AGIS study, with an MD change of 1.3 dB 25…”
Section: Discussionmentioning
confidence: 86%
“…The authors of GPA have attributed this same fact21 to the greater sensitivity of the Progressor program with respect to the GCP software 22. However, recent studies have observed that the change in MD after cataract operation is small,23 In patients with glaucoma, using the SITA-standard strategy we have observed that cataract removal improves MD by about 1.2 dB on average 24. A similar result was reported after cataract surgery in the AGIS study, with an MD change of 1.3 dB 25…”
Section: Discussionmentioning
confidence: 86%
“…The effect of cataract extraction on PSD remains controversial. While a few reports did not show any PSD changes [42,43], other reports showed PSD deterioration after cataract surgery in patients with glaucoma [39,40]. A diffuse sensitivity loss due to cataract may mask focal defects in glaucomatous VFs.…”
Section: Discussionmentioning
confidence: 99%
“…As MD is calculated based on the total deviation map, it is believed that its inherent limitation is the compound effect of diffuse depression caused by coexisting cataract. Therefore, the significant improvement in MD after cataract extraction is not a surprising result, and this has been proven in other studies [6][7][8][9][10][11].…”
Section: Effect Of Cataract Extraction On Visual Fieldmentioning
confidence: 58%
“…Previous studies [2,[6][7][8][9][10][11] on open angle or mixed glaucomatous eyes have shown statistically significant changes in visual field parameters after cataract extraction. Similarly, cataract extraction was found to have significant impact on RNFL thickness measurements [12][13][14][15].…”
Section: Introductionmentioning
confidence: 93%